Function

Algebra Level 2

If f ( x ) = 2 x 4 4 f(x) = 2x^4 - {4} and g ( x ) = x 2 2 g(x) = \sqrt{\dfrac{x-2}{\sqrt{2}}} , then what is the value of f g ( 5 ) f \circ g(5) ?

5 5 2 2 2 \sqrt{2} 5 \sqrt{5}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Sep 15, 2017

f g ( 5 ) = f ( g ( 5 ) ) = f ( 5 2 2 ) = f ( 3 2 ) = 2 ( 3 2 ) 4 4 = 2 ( 9 2 ) 4 = 9 4 = 5 \begin{aligned} f \circ g (5) & = f(g({\color{#D61F06}5})) \\ & = f \left(\sqrt{\frac {{\color{#D61F06}5}-2}{\sqrt 2}} \right) \\ & = f \left({\color{#3D99F6}\sqrt{\frac 3{\sqrt 2}}} \right) \\ & = 2\left({\color{#3D99F6}\sqrt{\frac 3{\sqrt 2}}} \right)^4 - 4 \\ & = 2\left(\frac 92 \right) - 4 \\ & = 9 - 4 \\ & = \boxed{5} \end{aligned}

@Sakib Nazmus , use f \circ g f g f \circ g

Chew-Seong Cheong - 3 years, 8 months ago

@Chew-Seong Cheong didn't understand the fourth line.

Nazmus sakib - 3 years, 8 months ago

Log in to reply

Thanks. A typo. I have corrected it.

Chew-Seong Cheong - 3 years, 8 months ago

g ( 5 ) = 5 2 2 = 3 2 g(5)=\sqrt{\dfrac{5-2}{\sqrt{2}}}=\sqrt{\dfrac{3}{\sqrt{2}}}

f g ( 5 ) = 2 ( 2 2 ) 4 4 = 2 ( 3 2 ) 2 4 = 2 ( 9 2 ) 4 = 9 4 = f \circ g(5)=2\left(\sqrt{\dfrac{2}{\sqrt{2}}}\right)^4-4=2\left(\dfrac{3}{\sqrt{2}}\right)^2-4=2\left(\dfrac{9}{2}\right)-4=9-4= 5 \large{\color{#D61F06}\boxed{5}}

You made a simple mistake. It should be g ( 5 ) = 5 2 2 = 3 2 g(5)=\sqrt{\dfrac{5-2}{\sqrt{2}}}=\sqrt{\dfrac{3}{\sqrt{2}}} and f g ( 5 ) = 2 ( 3 2 ) 4 4 f \circ g(5)=2\left(\sqrt{\dfrac{3}{\sqrt{2}}}\right)^4-4

Nazmus sakib - 3 years, 8 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...